The Influence of Word Of Mouth, Competitive Advantage And Brand Image Against The Decision to Use on Transportation Corporate - Meida Ratna Sari; Mudji Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine and analyze the effect of word of mouth, competitive advantage and brand image on the decision to use expeditionary services at PT. Lintas Samudra Jaya Expres. This research uses a quantitative approach. The population in this study are customers who are bound by a contract with PT. Lintas Samudra Jawa Express, while the probability sampling technique using the Slovin formula obtained a sample of 93 respondents. The data analysis technique was performed using multiple linear regression, and hypothesis testing was carried out by partial test, simultaneous test and multiple determination coefficient test with the help of SPSS version 25. The results show that: 1) word of mouth affects the decision to use shipping services, 2) competitive advantage affects the decision to use shipping services, 3) brand image affects the decision to use shipping services, and 4) word of mouth, competitive advantage and brand image affects the decision to use courier services at PT. Lintas Samudra Jaya Espress.